Aggregation-induced circularly polarized luminescence of an (R)-binaphthyl-based AIE-active chiral conjugated polymer with self-assembled helical nanofibers. Issue 13 (6th February 2015) - Zhang, Shuwei; Sheng, Yuan; Wei, Guo; Quan, Yiwu; Cheng, Yixiang; Zhu, Chengjian
Abstract : An AIE-active chiral conjugated polymerP-1 exhibited aggregation-induced circularly polarized luminescence. The TEM and AFM images show thatP-1 self-assembled into helical nanofibers during aggregation. Abstract : Four main-chain chirality conjugated polymers incorporating ( R )-1, 1′-binaphthyl and tetraphenylethene moieties were designed and then synthesized via Sonogashira or Suzuki reactions. All the polymers showed typical AIE phenomena, but do not have circularly polarized luminescence (CPL) properties in THF solutions. However, after aggregation in THF–water mixtures, the polymer linked with triple-bonds at the 3, 3′-positions of ( R )-1, 1′-binaphthyl moieties, P-1, exhibited obvious CPL, while other three polymers did not have any CPL signal. Moreover, the repeating unit ofP-1 had no CPL signals in both the dispersed and aggregated states, indicating that the polymer chain plays an important role in the aggregation-induced CPL, which can be tuned by changing the content of water in THF medium. The intensity of the aggregation-induced CPL reached the maximum when the water fraction was 80 vol%. The TEM and AFM images clearly show thatP-1 self-assembled into helical nanofibers during the aggregation, and the morphologies of the aggregates could be changed regularly by altering the water content of the solution. These results indicate a possible relationship between the CPL intensities and the morphologies of the aggregates.